Cytospora and Diaporthe Species Associated With Hazelnut Canker and Dieback in Beijing, China - Gao, Hong; Pan, Meng; Tian, Chengming; Fan, Xinlei (Frontiers in Cellular and Infection Microbiology, 2021)
Hazelnut (Corylus heterophylla Fisch.) is an important nut crop in China but has been declining owing to the destructive effects of fungal branch cankers and dieback. The identification and management of these pathogens are difficult because of the lack of attention to branch cankers and insufficient understanding of phylogenetic and overlapping morphological characteristics of the pathogens. In total, 51 strains were isolated from Chinese wild hazelnut in this study, and three species of Cytospora and two of Diaporthe were identified through morphological observation and multi-locus phylogenetic analysis (ITS, act, rpb2, tef1-α, and tub2 for Cytospora; ITS, cal, his3, tef1-α, and tub2 for Diaporthe). Three new species, Cytospora curvipora, C. corylina, and Diaporthe corylicola, and two known species, Cytospora leucostoma and Diaporthe eres, grew at 5–30 °C and a pH of 3.0–11.0, with optimum growth at approximately 25 °C and pH 4.0–7.0. Additionally, the effects of six carbon sources on mycelial growth were investigated. This study explored the main pathogenic fungi species of Corylus heterophylla, completed the corresponding database of pathogenic fungi information, and clarified their biological characteristics. Moreover, the results of this study provide a theoretical basis for C. heterophylla disease management and prevention in China.